Employees’ Attitudes toward Life and their Happiness at Work: Examining Government Organizations in the UAE - Al Nuaimi, Asma (Journal of Ecohumanism, 2024)
Although there is a wealth of happiness literature from both Western and Eastern experiences and perspectives, research on happiness in the workplace especially within the Arab region and high-context cultures—is limited. This study is an attempt to encourage happiness research in workplaces in the Middle East. Focusing on government organizations in the United Arab Emirates, this study aims to influence government organizations’ strategy planning and implementation regarding long-term impact on happiness levels. In particular, this study investigates how government organization employees’ personal attitudes toward life affect their feelings toward work. The research employed a quantitative analysis (questionnaire), thereby providing a detailed analysis of questionnaire responses across four government organizations at the functional level. Data were collected from 140 employees in four government organizations in the UAE over a period of four months. By performing data analysis using a quantitative tool to recognize the gaps between attitudes toward life and happiness levels at work in a high-context culture, this study makes recommendations to increase happiness levels across organizations in the long run. The study results reveal that participant employees largely exhibited a positive life outlook, which can be attributed to the UAE’s HC culture. Social life in the UAE is always active, with numerous family gatherings and social occasions, which can be considered a source of happiness. This study’s findings emphasize the necessity of correlating how individuals’ life attitudes positively or negatively influence their happiness levels at work.